2014
DOI: 10.3390/inorganics2030455
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experiments: Optimizing the Polycarboxylation/Functionalization of Tungsten Disulfide Nanotubes

Abstract: Design of experiments (DOE) methodology was used to identify and optimize factors that influence the degree of functionalization (polycarboxylation) of WS 2 INTs via a modified acidic Vilsmeier-Haack reagent. The six factors investigated were reaction time, temperature and the concentrations of 2-bromoacetic acid, WS 2 INTs, silver acetate and DMF. The significance of each factor and the associated interactive effects were evaluated using a two-level factorial statistical design in conjunction with statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Realizing the important ramifications of this new derivatization method, we undertook in parallel with the present study an optimization study [50], via design of experiments (DoE) methodology of several reaction parameters to maximize the yield of polyCOOH f-INT-WS 2 . In addition to finding optimum values of reaction factors, an interaction analysis indicated that reaction parameters might be adjusted to tune the level of poly-carboxylation obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Realizing the important ramifications of this new derivatization method, we undertook in parallel with the present study an optimization study [50], via design of experiments (DoE) methodology of several reaction parameters to maximize the yield of polyCOOH f-INT-WS 2 . In addition to finding optimum values of reaction factors, an interaction analysis indicated that reaction parameters might be adjusted to tune the level of poly-carboxylation obtained.…”
Section: Introductionmentioning
confidence: 99%
“…This functionalization method was optimized by the design-of-experiment (DoE) methodology. [ 26 ] This method is included, along with the method described in this paper and with other functionalization methods developed in our group, in a U.S. provisional patent application. [ 27 ] In this paper, we present a new method for the functionalization of WS 2 INTs with conformal, humin-like coatings of different thicknesses.…”
Section: Introductionmentioning
confidence: 99%
“…These iminium salts are electrophilic species that can be attacked by the surface sulfur atoms of the WS 2 INTs. This functionalization method was optimized by the design‐of‐experiment (DoE) methodology . This method is included, along with the method described in this paper and with other functionalization methods developed in our group, in a U.S. provisional patent application…”
Section: Introductionmentioning
confidence: 99%
“…However, in many cases, the adhesion between a nanoparticle and the polymer matrix is limited to the weak van der Waals interaction and could be enhanced by means of covalent bonding at the nanoparticle-polymer interface. Surface functionalization of IFs or INTs, as reported by Raichmann et al [10], could provide stronger adhesion of nanoparticles with the polymer matrix. The emphasis in this direction was given to the non-trivial functionalization of the hydrophobic WS2 nanotubes by hydrophilic carboxyl groups, which could further stimulate the fabrication of hydrophilic polymer composites or ceramics.…”
mentioning
confidence: 87%